Patient Perspectives on the Use of Digital Technology to Help Manage Cystic Fibrosis. (23rd January 2023) - Watanabe, Alexandre H.; Willis, Connor; Ragsdale, Russell; Biskupiak, Joseph; Moore, Karlene; Brixner, Diana; Young, David
Abstract : Background . Digital health technologies (DHTs) have shown potential to improve health outcomes through improved medication adherence in different disease states. Cystic fibrosis (CF) requires care coordination across pharmacies, patients, and providers. DHTs can potentially support patients, providers, and pharmacists in diseases like CF, where high medication burden can negatively impact patient quality of life and outcomes. Methods . In this prospective cohort study, a CF-specific mobile application (Phlo) was distributed to adults with CF who received care at the University of Utah Cystic Fibrosis Center, used an iPhone, and filled prescriptions through the University of Utah Specialty Pharmacy services. Participants were asked to use Phlo for 90 days with an optional 90-day extension period. Participants completed four surveys at baseline and after 90 days. Changes in patient-reported outcomes, adherence, clinical outcomes, and healthcare resource utilization from baseline to 90 days were tracked. Results . Phlo allowed users to track daily regimen activities, contact their care team, receive medication delivery reminders, and share progress with their healthcare team. A web-based dashboard allowed the care team to review reported performance scores from the app. Most patients (67%) said the app improved confidence in and motivation for continuing their regimen. The most important reported benefit of Phlo was having a single location to manage their whole routine. Conclusions . Phlo is a mobile health technology designed to help patients with CF manage their treatment regimen and improve patient-provider communication.